2009
DOI: 10.1590/s0034-72992009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação longitudinal do ECAP registrado em crianças usuárias de implante coclear

Abstract: In children with cochlear implant (CI), the recording of the electrically evoked compound action potential (ECAP) of the auditory nerve represents an option to assess changes in auditory nerve responses and the interaction between the electrode bundle and the neural tissue over time. Aim: To study ECAP in children during the first year of CI use. Materials and methods: The ECAP characteristics have been analyzed in 13 children implanted younger than three years of age. Series study. Results: During the first y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Some studies refer that in a long period of auditive deprivation can negatively influence the speech perception tests and that the period of auditive deprivation is directly proportional to the lowest performance in speech recognition 5,16,17 . The clinical analysis in this study evidenced that the early activation of CIs, that is, a smaller period of auditive deprivation is an important variable in the test performance.…”
mentioning
confidence: 99%
“…Some studies refer that in a long period of auditive deprivation can negatively influence the speech perception tests and that the period of auditive deprivation is directly proportional to the lowest performance in speech recognition 5,16,17 . The clinical analysis in this study evidenced that the early activation of CIs, that is, a smaller period of auditive deprivation is an important variable in the test performance.…”
mentioning
confidence: 99%
“…In these literature findings, the CI surgery was performed with participants from different age groups. Only in the study of Tanamati et al 18 a younger age at surgery was observed, before 3 years, but with no statistical significance. The age at CI surgery (23.50 months) and the bilateral stimulation of the hearing nerve can justify the significant finding during the first three months in our population.…”
Section: Discussionmentioning
confidence: 83%
“…However, in the studies of Tanamati et al, 18 Hughes et al, 6 Thai Van et al, 10 and Muhaimeed et al 19 there were no statistically significant differences in the T-NRT threshold during the first year of device programming. Lai et al 16 also found no significant difference in this measure in the first 15 months of device use.…”
Section: Discussionmentioning
confidence: 90%
“…As in CI-evoked EABR, electrical compound action potential (ECAP) has been shown to grow with CI stimulation. An absent ECAP response is associated with poor CI performance in children with auditory neuropathy [39, 41, 42].…”
Section: Discussionmentioning
confidence: 99%